2018
DOI: 10.3389/fimmu.2018.01819
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of the Minor Histocompatibility Antigen Landscape Based on the 1000 Genomes Project

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is routinely used to treat hematopoietic malignancies. The eradication of residual tumor cells during engraftment is mediated by donor cytotoxic T lymphocytes reactive to alloantigens. In a HLA-matched transplantation context, alloantigens are encoded by various polymorphic genes situated outside the HLA locus, also called minor histocompatibility antigens (MiHAs). Recently, MiHAs have been recognized as promising targets for post-transplantation T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
(78 reference statements)
1
12
0
Order By: Relevance
“…The SNPs when compared to the mutations used to estimate TSA, are much larger in number, indicating that mHA may provide the dominant antigen background in terms of generating alloreactivity following HCT. Similar data regarding the extent of genomic variation between transplant donors and recipients have been reported by other groups investigating genomic variation in transplant recipients, in both solid organ transplants (48) and in HCT (49)(50)(51)(52)(53), as well as in models predicting GVL specific libraries (54). This abundance of SNPs across the exome in unique HCT donor-recipient pairs is an eye-opening finding compared to the average 10 mutations per hematologic neoplasm.…”
supporting
confidence: 75%
“…The SNPs when compared to the mutations used to estimate TSA, are much larger in number, indicating that mHA may provide the dominant antigen background in terms of generating alloreactivity following HCT. Similar data regarding the extent of genomic variation between transplant donors and recipients have been reported by other groups investigating genomic variation in transplant recipients, in both solid organ transplants (48) and in HCT (49)(50)(51)(52)(53), as well as in models predicting GVL specific libraries (54). This abundance of SNPs across the exome in unique HCT donor-recipient pairs is an eye-opening finding compared to the average 10 mutations per hematologic neoplasm.…”
supporting
confidence: 75%
“…As reported by Bykova et al (30), SNPs with a high probability of mismatch between patient and donor have allele frequencies between 0.15 and 0.47. Our data showed that for seven common HLAs, all minor histocompatibility antigens encoded by SNPs with these allele frequencies can be detected with the new panel of EBV-LCLs from the 1000 Genomes Project.…”
Section: Discussionmentioning
confidence: 69%
“…In theory, selective depletion of HLA-A and HLA-B while preserving HLA-C on CAR T-cells could potentially limit the essential pool of allogeneic "off-the-shelf" cell products to several dozens or even less. Nevertheless, allogeneic cells with retained expression of either HLA class I or II still hold a significant threat of immunogenicity in a patient due to minor histocompatibility antigens (MiHAgs) [138] derived from near-infinite diversity of single nucleotide polymorphisms (SNPs) that vary in the donor and a patient [139]. These antigens contribute to GvHD (in hematopoietic stem cell transplantation) or transplant rejection (in solid organ recipients) and could also limit the persistence of allogeneic CAR T-cells.…”
Section: Universal Car T-cellsmentioning
confidence: 99%